2004
DOI: 10.1111/j.1439-0450.2004.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Immunohistochemical Study of Experimental Peste Des Petits Ruminants Virus Infection in Goats

Abstract: Peste des petits ruminants (PPR) is an emerging, economically important viral disease of goats and sheep in the Indian subcontinent. In the present investigation, 15 hill goats were experimentally infected with 2 ml of 10% splenic suspension of a virulent isolate of PPR virus (PPR/Izatnagar/94) that had caused heavy mortality (>75%) in goats during 1994 outbreaks in northern India. More than 86% (13 of 15) animals died between 9 and 13 days post inoculation at the height of temperature or when temperatures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 21 publications
17
67
0
Order By: Relevance
“…The clinical features or signs are better described under experimental condition rather than the natural infection. Both in natural as well experimental PPR infection, the incubation period ranged from 2 to 6 days [74,75,95,153]. In experimentally infected kids, the first clinical sign of pyrexia (40.6-44.2°C) was observed on days 5, followed by diarrhea (between day 5 and 8) and death within 10 days [143].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical features or signs are better described under experimental condition rather than the natural infection. Both in natural as well experimental PPR infection, the incubation period ranged from 2 to 6 days [74,75,95,153]. In experimentally infected kids, the first clinical sign of pyrexia (40.6-44.2°C) was observed on days 5, followed by diarrhea (between day 5 and 8) and death within 10 days [143].…”
Section: Diagnosismentioning
confidence: 99%
“…In experimentally infected kids, the first clinical sign of pyrexia (40.6-44.2°C) was observed on days 5, followed by diarrhea (between day 5 and 8) and death within 10 days [143]. Further, Kumar et al [75] observed rise in the temperature at 3rd days post infection (dpi) (104.5°F) to 10th dpi with general congestion, erosion and ulceration of oral mucosa in the challenged goats. The different stages of the disease are (i) incubation period, (ii) Prodromal phase (febrile), (iii) mucosal phase (ocular and nasal discharges, hyperaemia of conjunctiva and mucosa of anterior nares, and erosions on the tongue, palate, lips and other parts of the oral mucosa- Fig.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,9,12,27,28 Among the characteristic histopathologic findings of PPRV infection are syncytial cells in affected oral mucosa and lungs, as well as eosinophilic nuclear and cytoplasmic inclusion bodies, especially in the respiratory and/or alimentary tract epithelia. 6,8,12,21,28 Noncharacteristic pathologic findings, such as multifocal necrosis in the liver and inclusion bodies in hepatocytes and abomasal epithelial cells, are rarely reported. 2,32 Little is known about the resemblance of the pathologic findings of PPRV infection to those resulting from the other morbillivirus infections in terms of lesions in the central nervous system, kidney, and abomasum.…”
Section: Introductionmentioning
confidence: 99%
“…2,32 Little is known about the resemblance of the pathologic findings of PPRV infection to those resulting from the other morbillivirus infections in terms of lesions in the central nervous system, kidney, and abomasum. 11,21,28,32,33 The first PPRV infection in Turkey was reported in 4 sheep 2 , and since then many outbreaks have been reported. 23,24,32,34 Ö zkul et al 24 isolated PPR viruses from 2 separate field cases in Turkey.…”
Section: Introductionmentioning
confidence: 99%